Multiple Cross Displacement Amplification Combined with Gold Nanoparticle-Based Lateral Flow Biosensor for Detection of Vibrio parahaemolyticus - Wang, Yi; Li, Hui; Li, Dongxun; Li, Kewei; Wang, Yan; Xu, Jianguo; Ye, Changyun (Frontiers in Microbiology, 2016)
Vibrio parahaemolyticus (V. parahaemolyticus) is a marine seafood-borne pathogen causing severe illnesses in humans and aquatic animals. In the present study, multiple cross displacement amplification was combined with a lateral flow biosensor (MCDA-LFB) to detect the toxR gene of V. parahaemolyticus in DNA extracts from pure cultures and spiked oyster homogenates. Amplification was carried out at a constant temperature (62°C) for only 30 min, and amplification products were directly applied to the biosensor. The entire process, including oyster homogenate processing (30 min), isothermal amplification (30 min) and results indicating (approximate 2 min), could be completed within 65 min. Amplification product was detectable from as little as 10 fg of pure V. parahaemolytius DNA and from approximately 4.2×102 CFU in 1 mL of oyster homogenate. No cross-reaction with other Vibrio species and with non-Vibrio species was observed. Therefore, the MCDA-LFB method established in the current report is suitable for the rapid screening of V. parahaemolytius in clinical, food and environmental samples.